Muhammad Kazim’s Travelogue "A Season in Daman-e-Kooh" a Criticle Study - Irshad, Saira; Fatima, Sadaf; Abbas, Syed Azwar (sourcecoder, 2022)
Muhammad Kazim was born on August 4, in a Syed family in Ahmadpur Sharqiya Tehsil of the former state of Bahawalpur. Mohammad Kazim’s travelogue "A Season in the Mountains of Daman" is based on the history of Germany. On behalf of the office, Mohammad Kazim and two other members leave for one year for a diploma in German language. And it is a milestone in understanding the important places there. Mohammad Kazim has added color to the story thanks to the detail and excellent style. He is rich in creativity and has access to his expressions. Muhammad Kazim describes the situation very well through simple sentences. This travelogue is fascinating, informative and fascinating. Undoubtedly, Muhammad Kazim’s travelogue "A Season in Daman Koh" can be considered as an invaluable treasure for Urdu literature.